STEM APPROACH TO EDUCATION AND ITS PERSPECTIVES - Siqqikov Ilxomjon Melikuziyevich (Galaxy International Interdisciplinary Research Journal, 2024)
The article reports on STEM technologies, which are rapidly developing in the education system today. Opinions are expressed on the methods and advantages of making the most of this technology in a free education system.